A Modeling Study of Dislocation Behavior in InGaAs/GaAs (001) and InAlGaAs/GaAs (001) Heterostructures Utilizing Strained-Layer Superlattices. (3rd July 2019) - Islam, Md Tanvirul; Kujofsa, Tedi; Ayers, John E
Abstract : There have been a number of studies of dislocation filtering by strained-layer superlattices (SLSs) incorporated into semiconductor heterostructures. Despite the extensive nature of this body of work, a general understanding of the phenomenon has proved elusive, preventing wide application of SLS dislocation filters in practical devices. However, recent advances in the understanding of dislocation dynamics and the consequent development of detailed plastic flow models allow the prediction of threading dislocation density profiles in general semiconductor heterostructures. In this work, we have extended the usefulness of the plastic flow models by accounting for the weaving and zagging of dislocations at mismatched interfaces when calculating the effective interaction length for annihilation and coalescence reactions between dislocations. The refined plastic flow model has been applied to InGaAs/GaAs (001) and InGaAlAs / GaAs (001) heterostructures containing InGaAs and AlGaAs SLSs, and we have studied the dependence of the threading dislocation density profiles on the placement and design of the SLS. The refined model shows qualitative agreement with experimental results for SLS dislocation filters.